2020
DOI: 10.1002/jcu.22899
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS complexes are associated with subclinical left ventricular dysfunction in patients with Behcet's disease: Four‐dimensional speckle tracking echocardiography

Abstract: Background Behcet's disease (BD) is a chronic systemic inflammatory disease in which early detection of cardiac involvement is essential. The aim of this study was to assess the left ventricular (LV) functions in BD patients using four‐dimensional (4D) speckle tracking echocardiography (STE) and to test the correlation between LV dysfunction and the presence of QRS fragmentation. Methods This cross‐sectional study included 64 Behcet's patients and 48 healthy volunteers. The BD group was divided into two subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In a study by Hidayet et al. with Behçet's patients, it was found that GLS and GAS were impaired in the fQRS+ group, and there was a positive correlation between disease duration and the fQRS 32 . Similarly, in our study, longer disease duration correlates with worsened LV‐GCS and LV‐GAS, emphasizing the cumulative impact of elevated red blood cell counts on cardiac function over time.…”
Section: Di̇scussi̇onsupporting
confidence: 79%
“…In a study by Hidayet et al. with Behçet's patients, it was found that GLS and GAS were impaired in the fQRS+ group, and there was a positive correlation between disease duration and the fQRS 32 . Similarly, in our study, longer disease duration correlates with worsened LV‐GCS and LV‐GAS, emphasizing the cumulative impact of elevated red blood cell counts on cardiac function over time.…”
Section: Di̇scussi̇onsupporting
confidence: 79%
“…International Publisher between the chronic inflammatory state and cardiovascular diseases has been well established in the literature, pathological changes in ECG in inflammatory systemic diseases have gained interest in recent years [6]. In this concept, prolongation in QRS duration, which is related to an increased risk of arrhythmia, and the presence of fragmented QRS (fQRS), which is a sign of myocardial fibrosis has been widely studied in patients with chronic inflammatory systemic diseases [7][8][9][10]. To the best of our knowledge, fQRS and QRS duration have never been studied in IBD patients before.…”
Section: Ivyspringmentioning
confidence: 99%